A Regulatory Role of Apoptosis Antagonizing Transcription Factor in the Pathogenesis of Nonalcoholic Fatty Liver Disease and Hepatocellular Carcinoma. Issue 4 (4th March 2019) - Kumar, Divya P.; Santhekadur, Prasanna K.; Seneshaw, Mulugeta; Mirshahi, Faridoddin; Uram‐Tuculescu, Cora; Sanyal, Arun J.
Abstract : Hepatocellular carcinoma (HCC) is increasing as a cause of liver‐related mortality largely because of the growing burden of nonalcoholic steatohepatitis (NASH). The mechanisms of HCC development in nonalcoholic fatty liver disease (NAFLD) are incompletely understood. We initially identified apoptosis antagonizing transcription factor (AATF) to be associated with HCC in a mouse model of NASH that develops HCC without the addition of specific carcinogens. AATF, also called che‐1, is a transcriptional factor that is highly conserved among eukaryotes. AATF is known to be a central mediator of the cellular responses as it promotes cell proliferation and survival by inducing cell cycle arrest, autophagy, DNA repair, and inhibition of apoptosis. However, the role of AATF in NASH and HCC remains unknown. Here, we provide evidence for AATF as a contributory factor for HCC in NAFLD. AATF overexpression was further verified in human NASH and HCC and multiple human HCC cell lines. Tumor necrosis factor‐α (TNFα), known to be increased in NASH, induced AATF expression. Promoter analysis of AATF revealed a sterol regulatory element binding transcription factor 1‐c (SREBP‐1c) binding site; inhibition of SREBP‐1 by using specific inhibitors as well as small interfering RNA decreased TNFα‐induced AATF expression. AATF interacted with signal transducer and activator of transcription 3 to increase monocyte chemoattractant protein‐1 expression. AATF knockdown decreased cell proliferation, migration, invasion, colony formation, and anchorage‐dependent growth in HCC cell lines. Xenograft of QGY‐7703 HCC cells with AATF stably knocked down into nonobese diabetic scid gamma mice demonstrated reduced tumorigenesis and metastases. Conclusion: AATF drives NAFLD and hepatocarcinogenesis, offering a potential target for therapeutic intervention.